Pectin-Coated Curcumin-Chitosan Microparticles Crosslinked with Mg2+ for Delayed Drug Release in the Digestive System - Seung Won Hwang; Jae Sup Shin (International Journal of Polymer Science)
Curcumin-loaded chitosan-pectin microparticles based on polymeric microencapsulation were prepared by two methods to delay the release of curcumin in the digestive system, employing Mg2+ as a pectin-crosslinking agent for the first time. Pectin-coated curcumin-chitosan microparticles (C-g-PMg) and curcumin-loaded chitosan-pectin composite microparticles (C-PMg-g) were formulated, and their release profiles at pH 1.2 and at pH 6.8 were tested. The former (C-g-PMg) showed slower curcumin release profiles than the latter (C-PMg-g) because the C-g-PMg are composed of two layers, a chitosan-glutaraldehyde layer and a pectin-Mg2+ layer, which together hold the curcumin for a longer duration. Of the pectin-coated microparticles, those crosslinked with Mg2+ showed a slower release rate than those crosslinked with Ca2+, but the former showed a faster release rate at pH 6.8 in the presence of pectinase, acting as a promising drug delivery carrier for treating a colonic disease. The pectin layer and a pectin-crosslinking agent plays a vital role in prolonging the release of curcumin until pectin is degraded by pectinase.